A Review on Integration of Bicultural Identity - Xiao, Qinghui (Journal of Social Science and Humanities, 2024)
In the context of globalization, population mobility has surged, leading to more frequent interactions and collaborations among diverse cultural groups. This trend has facilitated the emergence of biculturalism, a phenomenon where an increasing number of individuals embody characteristics of two distinct cultures concurrently. Navigating the complex interplay between one's parental or heritage culture and the newly acquired culture poses significant challenges for bi-cultural individuals, necessitating a nuanced understanding and integration of their dual cultural identities. Bi-cultural identity integration represents a novel research paradigm within the field of identity studies. It is a trait-oriented concept that captures individual variations in how people perceive the relationship between their multiple identities. The concept of identity integration has been extensively applied in research on culture, demonstrating its positive impact on acculturation processes, mental health outcomes, and creative potential. By fostering an inclusive understanding of bicultural identity integration, researchers can contribute to the development of more culturally sensitive and inclusive societies.